An Evaluation of the Use of Deliberate Practice and Simulation to Train Interns in Requesting Blood Products. Issue 2 (April 2015) - Joyce, Kenneth M.; Byrne, Dara; O'Connor, Paul; Lydon, Sinéad M.; Kerin, Michael J.
<x xml:space="preserve">Abstract</x> Introduction Technical or practical skills deficits upon graduation from medical school are prevalent and contribute to increasing medical error. The current study sought to evaluate the efficacy of a simulation- and deliberate practice-based learning program for requesting blood products, delivered to newly graduated interns. Methods The requesting of blood products by a group of 27 "trained" interns was prospectively compared with that of a group of 30 "untrained" interns throughout the first 13 weeks of internship at an Irish teaching hospital. Results Our analysis showed that the training intervention reduced the risk of a rejected sample by 65% as compared with interns who did not receive the training. Moreover, the risk of a rejected sample for trained interns was 45% lower than for much more experienced doctors. The untrained interns required more than 2 months of clinical experience to reach an error rate that was not significantly different from that of the trained interns. Conclusions These findings indicate that skills acquired through deliberate practice generalized to the clinical setting led to a significant reduction in blood product prescribing errors.